Vascular Birthmarks as a Clue for Complex and Syndromic Vascular Anomalies - Diociaiuti, Andrea; Paolantonio, Guglielmo; Zama, Mario; Alaggio, Rita; Carnevale, Claudia; Conforti, Andrea; Cesario, Claudia; Dentici, Maria Lisa; Buonuomo, Paola Sabrina; Rollo, Massimo; El Hachem, May (Frontiers in Pediatrics, 2021)
Vascular birthmarks are common in neonates (prevalence: 20-30%) and mostly incidental findings sometime with spontaneous regression (salmon patch, nevus simplex). Capillary malformations are found in about 1% and infantile hemangiomas in 4% of mature newborns. Vascular malformations are classified according to their most prominent vessel type. The term “capillary malformation” (port wine stain) includes a wide range of vascular lesions with different characteristics; they may be isolated or part of specific syndromic conditions. Part of the infantile hemangiomas and of the vascular malformations may require treatment for functional or cosmetic reasons, and in rare cases investigations are also necessary as they represent a clue for the diagnosis of complex vascular malformation or tumors associated with extracutaneous abnormalities. Complex vascular malformations are mostly mosaicism due to early somatic mutations. Genetic advances have led to identify the main pathogenic pathways involved in this disease group. Diffuse capillary malformation with overgrowth, Klippel Trenaunay syndrome, CLAPO syndrome, CLOVES syndrome and megalencephaly-capillary malformation belongs to the PIK3CA-related overgrowth. Capillary malformation-arteriovenous malformations underlie a fast-flow vascular malformation, sometimes manifesting as Parkes-Weber syndrome. Recognition of these different types of capillary vascular stains is sometimes difficult; however, associated findings may orient the clinicians while genetic testing may confirm the diagnosis. Lymphatic malformation frequently manifests as large masses that compress and/or infiltrate the surrounding tissues, representing a neonatal emergency when airways are involved. Infantile hemangiomas may cause functional and/or permanent esthetical damage, depending on their localization (such as periorbital area, lip, nose); Large (more than 5 cm) infantile hemangiomas with a segmental distribution can be associated with obstruction or malformations of the underneath organs with complications: PHACE syndrome, LUMBAR/SACRAL syndrome, beard infantile hemangioma. In our review, we discuss controversies regarding the international classification and emerging concepts in the field of vascular anomalies. Finally, we discuss potential developments of new, non-invasive diagnostic techniques and repurposing of target therapies from oncology. Complex and/or life-threatening vascular tumours and malformations are extremely rare events and they represent a considerable therapeutic challenge. Early recognition of clinical signs suggestive for a specific disease may improve therapeutic outcomes and avoid severe complications.